Teachers' and learners' perceptions towards the use of frog VLE in the teaching and learning of reading comprehension - Siti Noor Farhana binti Zaipul Bahari (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The development of ICT provides many useful and effective tools such as wikis, blogs, synchronous and asynchronous communication. The Malaysian Ministry of Education (MOE) has introduced an internet integrated application, Frog Virtual Learning Environment (Frog VLE) in 2013 that allows teaching, learning, collaboration and administration to take place. After a year and a half of its implementation, this study attempts to understand the perceptions of Malaysian primary school teachers and learners towards an Internet integrated application, Frog Virtual Learning Environment (Frog VLE) application in reading comprehension lessons at SK (1) Selayang Baru (Malaysia), using the Technology Acceptance Model (TAM) framework. The sample consisted of two ESL teachers and 50 intermediate to advanced Year 6 ESL pupils. A mixed method was employed in analysing the triangulated data collected using questionnaires, interviews and observations. Subsequently, the data obtained from the questionnaire were analyzed quantitatively and the data from the interviews and observations were reported descriptively. The findings of the study reveal that both teacher and learner respondents perceived Frog VLE as a useful tool and easy to use. The findings also suggested that all respondents had positive attitudes towards using it and look forward to using Frog VLE more often in the future. However, results also indicate that their actual usage was limited due to limited ICT facilities available at the school and home. Based on the findings, the study recommends that ESL educators adopt Frog VLE to teach reading comprehension as well as other English language skills.